2014
DOI: 10.1097/dcr.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BMI on Postoperative Outcomes in Patients Undergoing Proctectomy for Rectal Cancer

Abstract: Obese and underweight patients undergoing proctectomy for neoplasm are at a higher risk for postoperative complications and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 23 publications
6
30
2
2
Order By: Relevance
“…In our study, the physical status (ASA) was worse in those patients, which also showed more comorbidities, especially cardiovascular risk factors and diabetes mellitus (data not shown). These findings are not surprising and have been widely described in the literature [2,[13][14][15].…”
Section: Impact Of Obesitysupporting
confidence: 77%
See 2 more Smart Citations
“…In our study, the physical status (ASA) was worse in those patients, which also showed more comorbidities, especially cardiovascular risk factors and diabetes mellitus (data not shown). These findings are not surprising and have been widely described in the literature [2,[13][14][15].…”
Section: Impact Of Obesitysupporting
confidence: 77%
“…In our analysis, 2.1% of all patients were underweight, compared to national population data of 0.1-0.2% in men and 0.2-1.9% in women depending on the age group of 60-69 or 70-79 years, respectively [12]. Preoperative weight loss is more common in underweight patients than in others [13,17]. Prospective randomized controlled trials, in which parameters of malnutrition are also analyzed, are necessary for further investigation of this topic.…”
Section: Impact Of Underweightmentioning
confidence: 45%
See 1 more Smart Citation
“…A obesidade é atribuída como fator de pior prognóstico para pacientes com neoplasias gastrintestinais, inclusive câncer retal, para os desfechos de curto prazo, tais como maior propensão ao aparecimento de fístulas e complicações relacionadas à ferida operatória (22,23,57,58,59,60 pacientes com baixo peso apresentam maior risco de mortalidade no pós-operatório quando comparados a pacientes com sobrepeso ou obesidade moderada (23,64).…”
Section: Tratamento Cirúrgico Oncológico Retalunclassified
“…Este padrão mostra que os piores desfechos no pós-operatório associam-se com os extremos do IMC, ou seja, pacientes com baixo peso ou pacientes com obesidade severa, e é comumente chamado de padrão em "forma de U" (21,22).…”
Section: Tratamento Cirúrgico Oncológico Retalunclassified